Visual Acuity Outcomes and Influencing Factors in a Cohort of UK Real-World Diabetic Macular Oedema Patients During the First Two Years of Anti-VEGF Treatment - Qing Wen; Helene Karcher; David M. Wright; Samriddhi Buxy Sinha; Usha Chakravarthy; Catarina Santos; Franklin Igwe; Recivall Salongcay; Katie Curran; Tunde Peto (Pharmaceutics)
Background/Objectives: The visual acuity (VA) outcomes after the first and second years of anti-vascular endothelial growth factor (anti-VEGF) treatment in patients with diabetic macular oedema (DMO) were evaluated, and the factors associated with treatment success were investigated. Methods: Using Medisoft electronic medical records (UK), this retrospective cohort study analysed VA outcomes, changes, and determinants in DMO patients at year 1 and year 2 after initial anti-VEGF injection. Descriptive analysis examined baseline demographics and clinical characteristics, while regression models were used to assess associations between these factors and changes in VA. Results: 728 DMO patients (1035 eyes) treated with anti-VEGFs (ranibizumab, aflibercept, or bevacizumab) at the Northern Ireland Mater Macular Clinic from 2008 to 2021 were evaluated. The mean age was 64.5 (SD 12.8) years, and 59.6% were male. In the first year, the median annual injection number and interval were 6.0 (IQR 5.0–8.0) and 6.1 weeks (IQR 5.4–7.8), respectively, and in the second year, they were 3.0 (IQR 2.0–5.0) and 10.0 weeks (IQR 6.5–20.1). In the first two treatment years, 83.4% and 79.8% of eyes had improved/stable VA (ISVA) respectively. The injection number, interval, baseline VA, age, and proliferative diabetic retinopathy (PDR) significantly impacted VA outcomes. Conclusions: Our study confirms the effectiveness of anti-VEGF treatments in improving or maintaining vision for DMO patients, consistent with previous real-world clinical data. An elder age, a better baseline VA, low annual injection numbers (<5), and less frequent injection intervals (≥12 weeks) were negatively associated with ISVA success in the first two years. These findings have implications for managing patient expectations, allocating resources, and understanding DMO clinical management.